2001
DOI: 10.1210/mend.15.8.0672
|View full text |Cite
|
Sign up to set email alerts
|

A Free Carboxylate Oxygen in the Side Chain of Position 674 in Transmembrane Domain 7 Is Necessary for TSH Receptor Activation

Abstract: A specific H-bonding network formed between the central regions of transmembrane domain 6 and transmembrane domain 7 has been proposed to be critical for stabilizing the inactive state of glycoprotein hormone receptors. Many different constitutively activating TSH receptor point mutations have been identified in hyperfunctioning thyroid adenomas in the lower portion of transmembrane domain 6. Position D633 in transmembrane domain 6 of the human TSH receptor is the only one in which four different constitutivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 50 publications
3
39
0
Order By: Relevance
“…In this mode of interaction the polar O ␊ atom of Asn-7.49 is free and points toward the intracellular side (see below). This carboxylate oxygen has been suggested as necessary in TSHr activation (35).…”
Section: Resultsmentioning
confidence: 97%
“…In this mode of interaction the polar O ␊ atom of Asn-7.49 is free and points toward the intracellular side (see below). This carboxylate oxygen has been suggested as necessary in TSHr activation (35).…”
Section: Resultsmentioning
confidence: 97%
“…In previous studies, we (36) and others (45) have shown that D633 in the 6th TMD is involved in the H-bond network between the 6th TMD and the 7th TMD and therefore is important for TSHR activation. The substitution of D633 with a positively charged arginine locked the TSHR in a completely inactive state (36).…”
Section: Discussionmentioning
confidence: 78%
“…The substitution of D633 with a positively charged arginine locked the TSHR in a completely inactive state (36). The introduction of the D633K mutation also strongly reduced TSHR activity (Table 1), most likely also by disturbing the intramolecular H-bond network and lowering the mobility of the 6th and 7th TMD.…”
Section: Discussionmentioning
confidence: 99%
“…11C). The interhelical network of hydrogen bond between Leu-457, Asp-578, and Asn-619 has been shown to be highly conserved in all the three GpHR members as shown through the rearrangement of carboxylate oxygen of TSHR N674 (Asn-619 in LHR) with Asp-633 (Asp-578 in LHR), resulting in a switch between the activated and inactivated states (29). Control of such an interhelical molecular switch by modulating the ECLs has already been exploited in designing small molecule agonist for TSHR and LHR (19).…”
Section: Spatial Organization Of the Loops In The Resting And Hormonementioning
confidence: 99%